Fauré, through Boulanger, to Copland: The Nature of Influence - Edward R. Phillips (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
Using tonal and post-tonal analytical methods, this article examines two early songs of Aaron Copland and compares them with the music of Gabriel Fauré, in order to determine if the notion that the compositional techniques of the older composer had an influence on those of Copland is valid and worthy of further research. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part III).